Ectopic Eruption of Maxillary First Permanent Molars: Preliminary Results of Prevalence and Dentoskeletal Characteristics in Spanish Paediatric Population - Alexandra Helm; Andrea Martín-Vacas; Pedro Molinero-Mourelle; Antonia M. Caleya; Nuria E. Gallardo; María Rosa Mourelle-Martínez (MDPI AG, 2021)
The ectopic eruption of the maxillary first permanent molar (EEM) is a local alteration of dental eruption with a multifactorial aetiology. The aims of our study were to determine the prevalence of the EEM in children and to analyse whether there is a relationship between EEM and dento-skeletal characteristics. A total of 322 children were analysed with the Ricketts cephalometric study and descriptive and analytical statistical analysis was carried out. The prevalence of EEM was 8.7%, with no statistically significant differences regarding gender or location, but a higher prevalence in the 7-year-old age group (18.8%) and bilateral EEM was more prevalent than unilateral EEM (p < 0.05). The most frequent findings were a shortened anterior cranial base, a retroposition of the maxilla and a distal position of the upper permanent first molar in relation to the pterygoid vertical in children with EEM. No statistically significant differences were found regarding the cephalometric parameters except a decreased palatal plane in the bilateral EEM group and a distal upper incisor position in the EEM group (p < 0.05). In conclusion, the prevalence of the EEM was 8.7%, more frequently bilateral, and significantly in seven-year-old patients. Children with bilateral EEM have decreased palatal plane values and a more posterior position of the upper incisor.